A darkling plain - Reeve, Philip (Reeve, Philip. Mortal engines quartet, 2017)
Tom Natsworthy and his daughter Wren learn that the city of London is being secretly rebuilt after a major devastation. But hidden in the background is the evil Stalker Fang who is attempting to block its reconstruction as part of his plan to destroy the world. It may be too late for Tom and Wren to achieve a victory in a fight over the city.